Alfred Schnittke’s concert for piano and string orchestra the role of polystylistics in the formation of intoniation-character dramaturgy - Reshetilov, Bohdan (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
Creativity of A. Schnittke is tightly connected with polystylistics. This term has been studied many times by musicologists as a technique of musical composition. However, its important role in the context of the formation of intonation-character dramaturgy remains a white spot. The study of polystylistics in this context on the example of the Concerto for Piano and Strings by A. Schnittke (written in 1979) is the relevance of the study, because it reveals new clues in understanding the ideological concept. The main objective of the study is an analytical method in which dramaturgy is explored in the context of stylistics, which creates a fertile basis for the formation of a semantic understanding of a musical work. The aim of the article is to summarize the methods for isolating intonation-character spheres subordinated to polystylistics, with the help of which it becomes possible to form a new semantic result. Different methodology is used in the article: semiotic-structural — for detailed analytical observations on dramaturgy-compositional features of the work by A. Schnittke; comparative — for comparative analysis and contextual vision of intonation-character spheres within the framework of polystylistic dramaturgy; functional — for studying and generalization of composer technological means of expressiveness subordinated to polystylistics. To main results and conclusions of the research are included several positions. The cinematographic approach in the formation of dramaturgy as a technical composition of a musical composition is manifested in the assembly comparison of the intonation-character spheres. This principle of thinking is based on sharp changes in the stylistic foundations. Taking into account the abundance of use of “someone else’s” musical material in the author’s work, it is possible to typologies the polystylistic detections as follows: addressing to the achievements of different epochs expressed in the typical means of musical expressiveness; addressing to individual style traits and opening of specific composers; addressing to themes and intonations from works of other composers; use of monograms, codes, ciphers in music; addressing to different musical flows, etc. As a result of application of the claimed method of the research a new philosophicalreligious semantic result of A. Schnittke work is formed, which is the main significance of this article.